EPCO-26. PROJECT HOPE: "PEDIATRIC AND AYA HIGH-GRADE GLIOMA OMICS PROJECT"- A LONGITUDINAL MOLECULAR LANDSCAPE OF HIGH-GRADE GLIOMAS RESOLVED AT SINGLE-CELL LEVEL. (9th November 2020) - Jiang, Li; Hack, Olivia; Babikir, Husam; Shamardani, Karin; Liu, Ilon; Shaw, McKenzie; Cunliffe-Koehler, Kennedy; Resnick, Adam; Prados, Michael; Monje, Michelle; Diaz, Aaron; Filbin, Mariella
Abstract: High-grade gliomas (HGG) are among the most prevalent and fatal cancers in pediatric, adolescent, and young adult (AYA) patients. Especially understudied are older children and young adults, aged 16–39 years. Previously, we profiled primary pediatric HGGs through single-cell transcriptomics and identified the genetic, epigenetic and developmental programs that drive their malignant progression. However, the questions of how these programs compare to those in older HGG patients, what the mechanisms are by which these tumors ultimately evolve to drive recurrence and treatment resistance, and how distinct tumor cell subpopulations bidirectionally communicate with their microenvironment remain to be elucidated. In order to investigate these questions, we use single-nucleus RNA sequencing to compare 11 paired, matched high-grade gliomas at diagnosis and recurrence and 15 additional H3K27M primary and recurrent DMG samples in pediatric and AYA patients. In all tumors, we find both undifferentiated and differentiated tumor cells recapitulating distinct glial lineages, as well as diverse microenvironmental cell populations. When longitudinally comparing this tumor architecture within matched pairs, we find substantial differences in transcriptional program expressions. In particular, recurrent samples showed a higher proportion of cells expressing heat- shock proteins (HSPs) and a novel cancer cell program characterized by synaptic formation and neurotransmitter secretory processes, suggesting tumor progression- and treatment-related shifts. Ongoing sequencing and analysis will allow for unprecedented insight into the evolutionary dynamics of pediatric and AYA high-grade gliomas as well as delineate differences in the biology of DMGs occurring in different age groups. This multi-institutional project was funded by the National Institute of Health.